STRATEGI BERTAHAN RUMAH MAKAN SAMRAT ABADI PADA MASA PANDEMI COVID-19 DI KECAMATAN WANEA KOTA MANADO (Survival Strategy of Samrat Abadi Restaurant During the Covid-19 Pandemic in Wanea District, Manado City) - Jenifer Elias; Agnes E. Loho; Grace A. J. Rumagit (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2021)
This study aimed to identify the survival strategy applied by Samrat Abadi Restaurant during the Covid-19 pandemic. This research lasted for 3 months, starting from October to December 2020. The data sources used in this study were primary data and secondary data. Primary data were obtained from interviews with respondents using questionnaires, while secondary data were obtained from previous research literature. The data analysis method in this research was descriptive analysis. The respondents were the owner of the Samrat Abadi Restaurant, the Cashier, and the Chef. The results showed that Samrat Abadi Restaurant: (1) maintaining revenue/profit even though it decreasedÂ  but was still profitable, (2) reducing the number of employees and reducing operating hours to minimize costs, (3) maintaining the quality of the product both in terms of taste , as well as food portions, (4) utilizing Digital Marketing and collaborating with e-commerce through the Grab and Gojek applications, (5) collaborating with the Church to expand marketing networks, (6) building relationships with customers, (7) improving quality and service through consumer criticism and suggestions box as well as through the Whatsapp application.